STUDY OF PERSONAL PROFESSIONAL BURNOUT AND MOTIVATION IN THE CONDITIONS OF REMOTE PROFESSIONAL ACTIVITY - Zurabyan, Albert (Modern Psychology, 2023)
The years of the COVID-19 pandemic have changed the way we live. In this regard, many companies have switched to the remote format of work, which has put new problems and challenges in front of them. One of those challenges is ensuring professional security in IT usage. Today, the security of the professional person remains a priority for all organizations, and the use of IT, in this context, becomes more important. In the framework of the work, we referred to the psychological aspects of professional security, which have become more significant in terms of the ready implementation of IT under the conditions of the COVID-19 epidemic. We attempted to study the motives for the deployment of activities of the subjects who were forced to change the classical model of mental activity in the pandemic and post-pandemic conditions of COVID-19, observing its effect on the formation of psychological burnout. Accordingly, the purpose of the study is to study the influence of motivation in the implementation of professional activities on the formation of psychological burnout among teachers and IT specialists working in an online format: To achieve the research goal, we have set and solved the following tasks․ identify and justify possible psychological factors affecting the safety of the subject of professional activity to clarify the impact of the implementation of the IT solution on the security of the subject of professional activity to clarify the effects of motivations on the formation of psychological burnout of online educators and IT specialists During the implementation of the research, the method of canceling the syndrome of psychological burnout was applied, developed by A.A. Rukavishnikov and K. Zamfir’s "Professional Motivation Study" methodology modified by A. Reana. The results of the study made it possible to clearly note that teachers and IT specialists, regardless of the nature of the available motives, have high rates of emotional burnout; however, IT specialists with external positive or internal motives have these indicators mildly expressed.